Dropshipping in Batam Bonded Area: Tax Consultants' Challenges in Preventing Value Added Tax Disputes - Wismo Malaicanto, Totok Catur; Arpangi, Arpangi (Jurnal Hukum Khaira Ummah, 2025)
This research analyzes the complexity of Value Added Tax (VAT) implementation in dropshipping business practices within the Batam Bonded Zone, given the rapid growth of the digital economy and the nature of cross-jurisdictional transactions. This thesis aims to identify the f i scal compliance challenges faced by dropshipping actors and tax authorities, and to formulate policy recommendations that align with both positive legal frameworks and Sharia ethics. Using a juridical- normative approach enriched with empirical data through in-depth interviews, this study examines the inconsistencies of de minimis rules, the ambiguity in determining VAT' s point of incidence, and their implications for the principles of justice (adl) and legal certainty. The findings indicate that the current regulatory ambiguities create gharar (excessive uncertainty) which potentially reduces tax legitimacy in the eyes of Muslim taxpayers. Although specific mediation cases related to dropshipping VAT disputes in Bonded Zones are not widely documented, mediation is identified as a potential alternative dispute resolution mechanism that is more efficient and adaptive. This research concludes that regulatory harmonization between digital business dynamics and Sharia principles is highly necessary, and offers a comprehensive theoretical framework integrating positive law and Islamic ethical dimensions, with novelty in its specific analysis of the Batam Bonded Zone and the role of mediation as a solution.